2022
DOI: 10.1002/lio2.920
|View full text |Cite
|
Sign up to set email alerts
|

Demographic differences in the treatment of unilateral vocal fold paralysis

Abstract: Objective: To determine the impact of patient demographics and social determinants of health on treatment pathways for unilateral vocal fold paralysis (UVFP) at a tertiary laryngology clinic.Study design: Retrospective medical record review.Methods: Patient demographics (age, gender, race, ethnicity, and insurance status) were extracted for adults diagnosed with UVFP between 2009 and 2019. Odds ratios for the associations between sociodemographic factors and UVFP treatment pathways were determined by chi-squar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Their study included 1490 adult patients with 58% female, 97% non-Hispanic, and 54% publicly insured patients undergoing observation, voice therapy, injection laryngoplasty, thyroplasty, and reinnervation surgery. 43 They similarly found that males were more likely to undergo injection laryngoplasty than females (OR 1.32; CI 1.08-1.61) and that females were more likely to undergo voice therapy (OR 1.39; CI 1.09-1.76), although they found no gender association with surgical interventions. This supports the findings of Cohen et al that females had lower expenditures for a range of laryngeal disorders compared to males.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Their study included 1490 adult patients with 58% female, 97% non-Hispanic, and 54% publicly insured patients undergoing observation, voice therapy, injection laryngoplasty, thyroplasty, and reinnervation surgery. 43 They similarly found that males were more likely to undergo injection laryngoplasty than females (OR 1.32; CI 1.08-1.61) and that females were more likely to undergo voice therapy (OR 1.39; CI 1.09-1.76), although they found no gender association with surgical interventions. This supports the findings of Cohen et al that females had lower expenditures for a range of laryngeal disorders compared to males.…”
Section: Discussionmentioning
confidence: 96%
“…42 Another study by Patel et al found that gender, ethnicity, and insurance were associated with differences in UVFI treatment, however, clinical factors were not considered. 43 Confounding clinical factors need to be considered in multivariable logistic regression models so that adjusted weights determine the effect size of SDOH variables. 43 Our work adds to the existing literature investigating the effects of SDOH on the presentation and management of UVFI.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations